Tuning The Electronic Crime in Shade Directions Criminal Policy - Abd Al Alally Dweg, Mohammed; Abdul Reda Aflouk , Prof.Dr. Mohammed Ali (Basra studies journal, 2023)
In recent centuries, the world has witnessed the emergence of information technology and its continuous and unlimited development, and the positive aspects that it produced on human societies at various levels, making the world in a circle of continuous communication. Rather, the development of information technology was also reflected in administrative transactions, as it became an important tool in meeting the needs of the state. And society, however, the matter does not stop at this positive role only, but this development was exploited by criminals and became an outlet to commit their crimes, until the emergence of electronic crime, which corresponded to the direction of criminal policy at the national and international levels to confront this type of crime, but this The type of crime is completely different from the control of traditional crimes because of the many problems that it causes with regard to the procedural aspect, whether in terms of the investigation procedure, the examination of the crime scene, the inspection procedure, or the preservation and preservation of evidence. Default other than physical (traditional) crimes.